How Twitter advertising influences the purchase intentions and purchase attitudes of Indian millennial consumers?. (15th February 2022) - Ghouse, Suhail M.; Duffett, Rodney Graeme; Chaudhary, Monica
This research investigates the influence of Twitter advertising on the purchase intentions and purchase attitudes of the millennial internet users in India, as well as to assess if the usage and demographic variables had an influence on their buying intentions and buying attitudes. A convenient sample was used to survey 500 Indian millennials via self-administered structured questionnaires. The results reveal Twitter advertising has a positive impact on the purchase attitudes of Indian millennials. More experienced Twitter users; logged-on more frequently; spent fewer hours; followed a greater number of companies/brands; were female; and younger Indian millennial respondents had the most favourable perceptions towards Twitter advertising. The research findings will help traditional organisations to acknowledge and adapt their promotional strategies to include Twitter advertising in their marketing budgets. This study also contributes to attitudinal research literature in an Indian context, which lacks research in social media advertising featuring the millennial segment.